2018
DOI: 10.1159/000485120
|View full text |Cite
|
Sign up to set email alerts
|

Elderly-Onset Neuromyelitis Optica Spectrum Disorder with Pre-Existing Prednisone Allergy

Abstract: We present a case of an 82-year-old man with new-onset neuromyelitis optica (NMO) spectrum disorder, the treatment of which was complicated by a severe pre-existing prednisone allergy. His age caused much initial doubt about his diagnosis, and his corticosteroid allergy altered our management as we attempted to minimize risk to the patient. Our patient was a healthy 82-year-old, right-handed man who presented with sensory loss of the bilateral lower extremities and progressive, painless vision loss. MRI showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…(36.53 ± 16.26 years). Although mean age of the first presentation of optic neuritis in NMOSD group was younger than MS and idiopathic group, the oldest patient in the NMOSD group was 75 years old in our study, and there were several studies that reported NMOSD in elderly up to 90 years old [ 26 , 27 ]. For elderlies with optic neuritis, NMOSD should be taken into account, especially for elderlies with poor vision at the beginning.…”
Section: Discussionmentioning
confidence: 50%
“…(36.53 ± 16.26 years). Although mean age of the first presentation of optic neuritis in NMOSD group was younger than MS and idiopathic group, the oldest patient in the NMOSD group was 75 years old in our study, and there were several studies that reported NMOSD in elderly up to 90 years old [ 26 , 27 ]. For elderlies with optic neuritis, NMOSD should be taken into account, especially for elderlies with poor vision at the beginning.…”
Section: Discussionmentioning
confidence: 50%
“…Our cohort was similar to several previous studies in terms of AQP4 serostatus, female predominance, age at first episode of ON in each affected eye, laterality. 1,10,[15][16][17][18][19][20][21][22][23][24] Most of the affected eyes (37 eyes, 58.6%) in our study presented with BCVA at nadir < 20/400. This result was fairly similar to several other studies, which provides additional evidences that NMOSD-ON is typically severe.…”
Section: Discussionmentioning
confidence: 53%
“…Chronic use of corticosteroids may be particularly difficult among individuals with diabetes, hypertension, gastrointestinal diseases, or osteoporosis. Pulses of methylprednisolone or dexamethasone, or plasma exchange, may be an option for elderly people, particularly those who do not have good tolerance for chronic use of corticosteroids [23]. Use of azathioprine has been correlated with higher risks of toxicity, infection, and malignancies [24].…”
Section: Discussionmentioning
confidence: 99%